2021
DOI: 10.1002/jsfa.11473
|View full text |Cite
|
Sign up to set email alerts
|

Responses of tea plants (Camellia sinensis) with different low‐nitrogen tolerances during recovery from nitrogen deficiency

Abstract: BACKGROUND: Tea plants have high nitrogen (N) consumptions, whereas molecular and physiological responses of tea plants to N recovery are still unclear. RESULTS: By using non-invasive micro-test technology (NMT), 15 N tracer technique, ultra-performance liquid chromatography (UPLC), and transcriptome sequencing technology, we investigated the N recovery-induced changes in N absorptions, N tissue distributions, contents of free amino acids (FAAs), and global transcription of the low-N tolerant and intolerant te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Specifically, N deficiency caused pyruvate metabolism to be reprogrammed in soybean (Fataftah et al, 2018). The timing of N resupply can influence the N response and recovery capability of tea plant, as reported previously, AMTs and NRTs in tea plant played leading roles in restoration from N deficiency at 1 and 24 h post N resupply, respectively (Ruan et al, 2021), and pear root can also recover from nitrate deficiency at 24 h post nitrate resupply (Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Specifically, N deficiency caused pyruvate metabolism to be reprogrammed in soybean (Fataftah et al, 2018). The timing of N resupply can influence the N response and recovery capability of tea plant, as reported previously, AMTs and NRTs in tea plant played leading roles in restoration from N deficiency at 1 and 24 h post N resupply, respectively (Ruan et al, 2021), and pear root can also recover from nitrate deficiency at 24 h post nitrate resupply (Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 67%
“…Additionally, the absorption rate of NH 4 + by tea plant was reported to higher than that of NO 3 − in N resupply (Ruan et al, 2021). Gene co-expression analysis also showed that compared with NRT, AMT1;1 was more closely related to TS (Figure 7B).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Interestingly, although NIGT1/HRS1/HHO genes have been characterized as NO 3 – -induced genes ( Sawaki et al, 2013 ; Maeda et al, 2018 ), 6 out of 8 CsNIGT1/HRS1/HHO genes were significantly upregulated in response to NH 4 + treatment, indicating that CsNIGT1s are also involved in the tea plant response to NH 4 + treatment and might play important roles in nitrogen absorption and utilization in tea plant. Recently, numerous differentially expressed genes were identified via transcriptome sequencing in tea plant in response to nitrogen treatment ( Li et al, 2017 ; Ruan et al, 2021 ), and our results could provide valuable candidate genes for further studies on the transcriptional regulatory mechanism of the tea plant response to nutrients. Additionally, in this study, we found that the expression levels of several CsNIGT1/HRS1/HHO and CsPHR1/PHL1 genes were also regulated by stress treatments.…”
Section: Discussionmentioning
confidence: 88%
“…Overexpression of GmProT1 and 2 can affect the synthesis and response of proline and alleviate the damage of salt and drought stress to plants [37]. GsGAT gene expression levels increase the ability of Glu to convert to GABA and transport GABA to maintain high nitrogen availability in Camellia sinensis [38].…”
Section: Introductionmentioning
confidence: 99%